Interpretasi Lapisan Bawah Permukaan Sebagai Perencanaan Tempat Penyimpanan Sampah Di Desa Talumelito, Kabupaten Gorontalo - K Badaun, Nur Azizah; Zainuri, Ahmad; Akase, Noviar; Aris, Ayub Pratama (Journal of Applied Geoscience and Engineering, 2022)
The Talumelito waste storage area is located in Talumelito Village, Telaga Biru District, Gorontalo Regency which accommodates waste from various human activities. Organic and inorganic waste will become a breeding ground for diseases that are very dangerous for society and the environment. The purpose of this study was to determine the subsurface layer as an interpretation of the planning for the construction of a waste storage area and determine whether it is feasible or not. The resistivity geoelectric method of the Schlumberger configuration is one of the geophysical methods that is easy, inexpensive and efficient and does not damage the environment. The geoelectric method is a geophysical method used to identify the properties and physical conditions of the subsurface based on the resistivity values of the rock. This method utilizes variations in the resistivity values of the subsurface rocks to detect geological structures or subsurface rock formations. Based on an analysis of resistivity and geological electrical properties, the location of the planning for the construction of a waste storage area is at VES 2, VES 3, and VES 5 points. Where from the interpretation results the three VES points have bedrock rock layers with granite rock types. Meanwhile, at VES 1 and VES 4, there is a layer of sandstone under the top soil layer. VES 2, VES 3 and VES 5 points are suitable for waste storage because there are layers of waterproof rock. Whereas at VES 1 and VES 4 points it is not suitable for waste storage because the sandstone layer is a layer that has good permeability, so if there is liquid waste from garbage, the waste will contaminate groundwater.